2004
DOI: 10.1126/science.1092727
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Dynamics of Imprinted X Inactivation During Early Mouse Development

Abstract: The initiation of X-chromosome inactivation is thought to be tightly correlated with early differentiation events during mouse development. Here, we show that although initially active, the paternal X chromosome undergoes imprinted inactivation from the cleavage stages, well before cellular differentiation. A reversal of the inactive state, with a loss of epigenetic marks such as histone modifications and polycomb proteins, subsequently occurs in cells of the inner cell mass (ICM), which give rise to the embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
793
3
14

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 743 publications
(856 citation statements)
references
References 37 publications
26
793
3
14
Order By: Relevance
“…Previous studies had suggested that genes may be expressed at a lower level from the X p in preimplantation embryos. (11)(12)(13) The current papers (1)(2)(3) that we discuss here further challenge the view that both X chromosomes are expressed in early stages of development by providing clear evidence of X p inactivation in preimplantation embryos.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Previous studies had suggested that genes may be expressed at a lower level from the X p in preimplantation embryos. (11)(12)(13) The current papers (1)(2)(3) that we discuss here further challenge the view that both X chromosomes are expressed in early stages of development by providing clear evidence of X p inactivation in preimplantation embryos.…”
Section: Introductionmentioning
confidence: 76%
“…Partial Xist RNA coating of the X p during early development (green-black gradient) correlates with incomplete silencing of genes on the X p . (1,3) Cot-1 has been found to be excluded from the Xist domain at the 2-cell stage (1) and RNA PolII excluded from the Xist domain at the 4-cell stage (2) (pink). Acetylated histone H3 (H3Ac) and methylated histone H3 lysine 4 (H3K4Me) become excluded along with Cot-1 and RNA PolII from the Xist domain at the 8-cell stage (2) (orange).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations